Analytical solutions for geosynthetic tube resting on rigid foundation - Guo, Wei (2015)
Geosynthetic tubes inflated with water, clay slurry or sand have been widely used for large dike construction in land reclamation projects. In this paper, analytical solutions for geosynthetic tube resting on rigid foundation is presented by adopting an approach similar to that presented by Leshchinsky et al. (1996). The proposed method allows a quick preliminary design to be made for using a closed-form solution. To simplify the analysis, relationships between geometrical parameters and pumping pressure are established using numerical method. The analytical solutions were compared with several existing solutions and good agreements were achieved.